SEISMICITY AND CRUSTAL DEFORMATION PRECEDING THE JANUARY 1996 ERUPTIONS AT KARYMSKY VOLCANIC CENTER, KAMCHATKA - Zobin V.M.; Levina V.I.; Maguskin M.A. (My University, 2003)
Two explosive eruptions occurred on 2 January 1996 at Karymsky Volcanic Center (KVC) in Kamchatka, Russia: the first, dacitic, from the central vent of Karymsky volcano, and the second, several hours later, from Karymskoye lake in the caldera of Akademia Nauk volcano. The main significance of the 1996 volcanic events in KVC was the phreatomagmatic eruption in Karymskoye lake, which was the first eruption in this lake in historical time, and was a basaltic eruption at the acidic volcanic center. The volcanic events were associated with the 1 January Ms 6.7 (Mw 7.1) earthquake that occurred at a distance of about 9–17km southeast from the volcanoes just before the eruptions. We study the long-term (1972–1995) and short-term (1–2 January 1996) characteristics of crustal deformations and seismicity before the double eruptive event in KVC. The 1972–1995 crustal deformation was homogeneous and characterized by a gradual extension with a steady velocity. The seismic activity in 1972–1995 developed at the depth interval from 0 to 20km below the Akademia Nauk volcano and spread to the southeast along a regional fault. The seismic activity in January 1996 began with a short sequence of very shallow microearthquakes (M ~0) beneath Karymsky volcano. Then seismic events sharply increased in magnitude (up to mb 4.9) and moved along the regional fault to the southeast, culminating in the Ms 6.7 earthquake. Its aftershocks were located to the southeast and northwest from the main shock, filling the space between the two active volcanoes and the ancient basaltic volcano of Zhupanovsky Vostryaki. The eruption in Karymskoye lake began during the aftershock sequence. We consider that the Ms 6.7 earthquake opened the passageway for basic magma located below Zhupanovsky Vostryaki volcano that fed the eruption in Karymskoye lake.
Keywords: Kamchatka; Karymsky Volcanic Center; Seismicity; Deformations; 1996 eruptions